Interplay between stiffness and degradation of architectured gelatin hydrogels leads to differential modulation of chondrogenesis in vitro and in vivo. (15th March 2018) - Sarem, Melika; Arya, Neha; Heizmann, Miriam; Neffe, Axel T.; Barbero, Andrea; Gebauer, Tim P.; Martin, Ivan; Lendlein, Andreas; Shastri, V. Prasad
Graphical abstract: Abstract: The limited capacity of cartilage to heal large lesions through endogenous mechanisms has led to extensive effort to develop materials to facilitate chondrogenesis. Although physical-chemical properties of biomaterials have been shown to impact in vitro chondrogenesis, whether these findings are translatable in vivo is subject of debate. Herein, architectured 3D hydrogel scaffolds (ArcGel) (produced by crosslinking gelatin with ethyl lysine diisocyanate (LDI)) were used as a model system to investigate the interplay between scaffold mechanical properties and degradation on matrix deposition by human articular chondrocytes (HAC) from healthy donors in vitro and in vivo . Using ArcGel scaffolds of different tensile and shear modulus, and degradation behavior; in this study, we compared the fate of ex vivo engineered ArcGels-chondrocytes constructs, i.e. the traditional tissue engineering approach, with the de novo formation of cartilaginous tissue in HAC laden ArcGels in an ectopic nude mouse model. While the softer and fast degrading ArcGel (LNCO3) was more efficient at promoting chondrogenic differentiation in vitro, upon ectopic implantation, the stiffer and slow degrading ArcGel (LNCO8) was superior in maintaining chondrogenic phenotype in HAC and retention of cartilaginous matrix. Furthermore, surprisingly the de novo formation of cartilage tissue was promoted only in LNCO8. Since HAC cultured for only three days in the LNCO8 environment showed upregulation of hypoxia-associated genes, this suggests a potential role for hypoxia in the observed in vivo outcomes. In summary, this study sheds light on how immediate environment ( in vivo versus in vitro ) can significantly impact the outcomes of cell-laden biomaterials. Statement of Significance: In this study, 3D architectured hydrogels (ArcGels) with different mechanical and biodegradation properties were investigated for their potential to promote formation of cartilaginous matrix by human articular chondrocytes in vitro and in vivo. Two paradigms were explored ( i ) ex vivo engineering followed by in vivo implantation in ectopic site of nude mice and ( ii ) short in vitro culture (3 days) followed by implantation to induce de novo cartilage formation. Softer and fast degrading ArcGel were better at promoting chondrogenesis in vitro, while stiffer and slow degrading ArcGel were strikingly superior in both maintaining chondrogenesis in vivo and inducing de novo formation of cartilage. Our findings highlight the importance of the interplay between scaffold mechanics and degradation in chondrogenesis.